THE ISSUE OF “SOPHICALITY” IN THE SCIENCE AND ITS TIME-AND-SPACE MEASURE - Кисельов, Юрій (Human Geography Journal, 2016)
The contents of the scientific and philosophical categories such as “logicality” and “sophicality” (“sofiynist”) are lined. It is marked that each science in whole consists of a “logical” and “sophical” disciplines those are complimentary one to another. It is stressed that among the Earth sciences the “logical” and “sophical” complimentariness is shaped by geonomy and geosophy. The criteria of “sophicality” for a scientific discipline are noted. The issue of relativity between Earth space and Earth time in the context of geosophical researches is stand. Evinces of “sophicality” by the examples of Ukraine are marked.